Лінгвістичні особливості висвітлення військового дискурсу (на прикладі АТО) у ЗМІ - Татаренко, Катерина (Видавництво Львівської політехніки, 2015)
The research emphasizes on the peculiarities of translation of the linguistic manipulation phenomenon during armed conflicts. It is therefore also an interesting area of study to see how certain conflict is projected in the media and how the image of the conflict is constructed – an image that in the end can affect the individuals taking part of the information. The purpose of this study is to conduct a comprehensive analysis of linguistic peculiarities of representing ATO in the Eastern part of Ukraine in different mass media during the period from November 2014 till February 2015.
Keywords: лінгвістичні особливості; військовий дискурс; АТО; ЗМІ; маніпуляція; збройний конфлікт